How Catastrophic Innovation Failure Affects Organizational and Industry Legitimacy: The 2014 Virgin Galactic Test Flight Crash - Chai, Sen; Doshi, Anil R.; Silvestri, Luciana (Organization Science, 2022)
We examine how catastrophic innovation failure affects organizational and industry legitimacy in nascent sectors by analyzing the interactions between Virgin Galactic and stakeholders in the space community in the aftermath of the firm’s 2014 test flight crash. Following catastrophic innovation failure, we find that industry participants use their interpretations of the failure to either uphold or challenge the legitimacy of the firm while maintaining the legitimacy of the industry. These dynamics yield two interesting effects. First, we show that, in upholding the legitimacy of the industry, different industry participants rhetorically redraw the boundaries of the industry to selectively include players they consider legitimate and exclude those they view as illegitimate: detracting stakeholders constrain the boundaries of the industry by excluding the firm or excluding the firm and its segment, whereas the firm and supporting stakeholders amplify the boundaries of the industry by including firms in adjacent high-legitimacy sectors. Second, we show that, in assessing organizational legitimacy, the firm and its stakeholders differ in the way they approach distinctiveness between the identities of the industry and the firm. Detracting stakeholders differentiate the firm from the rest of the industry and isolate it, whereas the firm and supporting stakeholders reidentify the firm with the industry, embedding the firm within it. Overall, our findings illuminate the effects that catastrophic innovation failure has over high-order dynamics that affect the evolution of nascent industries.